Applying social cognition models to explain walking duration in older adults: the role of intrinsic motivation - Labudek, Sarah; Fleig, Lena; Jansen, Carl-Philipp; Kramer-Gmeiner, Franziska; Nerz, Corinna; Becker, Clemens; Klenk, Jochen; Schwenk, Michael (Journal of human kinetics, 2021)
This study examined the applicability of the health action process approach (HAPA) to walking duration in older adults and the added value of extending the HAPA by intrinsic motivation. Self-reports from older adults (N = 309; Mage = 78.7, 70-95 years) regarding activity-related intrinsic motivation and HAPA variables were collected at the baseline of a fall prevention intervention study. Walking duration at ≥3 metabolic equivalents of task was measured for 7 days via body-worn accelerometers. Two structural equation models with walking duration as a manifest outcome were specified. In both models, the model fit was acceptable, but intention and planning were not associated with walking duration. Intrinsic motivation was significantly related to most HAPA variables and walking duration. Variance explained for walking duration was R2 = .14 in the HAPA and R2 = .17 in the extended model. For explaining older adults’ walking duration, intrinsic motivation, but not HAPA-based intention and planning, seemed to be important.
Gesehen am 21.10.2021